Family, Gender, and Labour in the Greek Mines, 1860–1940 - Papastefanaki, Leda (International review of social history, 2020)
To date, research on work in the mines in Greece has ignored the significance of gender in the workplace, since mining is associated exclusively with male labour. As such, it is considered, indirectly, not subject to gender relations. The article examines the influence of family and gender relations on labour in the Greek mines in the period 1860–1940 by highlighting migration trajectories, paternalistic practices, and the division of labour in mining communities. Sources include: official publications of the Mines Inspectorate and the Mines and Industrial Censuses, the Greek Miners’ Fund Archive, British and French consular reports, various economic and technical reports by experts, literature and narratives, the local press from mining regions, and the Archive of the Seriphos Mines.